2018
DOI: 10.1002/ange.201803587
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Performance Improvement of the Oxygen Evolution Reaction in a Stable Bimetal–Organic Framework System

Abstract: ZuschriftenFigure 4. a) Initial structure of the Fe 2 Mcluster,followed by the adsorptiono fOH*, O*, and OOH* intermediates on the Fe site. The active site is marked by ad ashed circle. b) The free energy profile for the OER pathway and c) projected density of states of Fe 2 M-cluster. Red arrows denotedt he d-band center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…22,26 Recent studies further demonstrate the capabilities of heterometallic clusters as the nodes of multivariate MOFs for heterogeneous catalysis. [27][28][29][30] These findings suggest it highly promising to achieve both stability and reactivity of Co-MOF photocatalysts by introducing proper high-valent cations into Co(II) clusters as heterometallic nodes. Nevertheless, such Co-MOFs have been rarely reported so far, 31 mostly due to the challenging fabrications tending toward the mixtures of monometallic MOFs or incomplete substitutions in the metal nodes.…”
Section: Introductionmentioning
confidence: 97%
“…22,26 Recent studies further demonstrate the capabilities of heterometallic clusters as the nodes of multivariate MOFs for heterogeneous catalysis. [27][28][29][30] These findings suggest it highly promising to achieve both stability and reactivity of Co-MOF photocatalysts by introducing proper high-valent cations into Co(II) clusters as heterometallic nodes. Nevertheless, such Co-MOFs have been rarely reported so far, 31 mostly due to the challenging fabrications tending toward the mixtures of monometallic MOFs or incomplete substitutions in the metal nodes.…”
Section: Introductionmentioning
confidence: 97%
“…Benchmark OER catalysts.While an initial overview of MOF OER catalysts demonstrates competitive, if not superior activity to non-MOF OER catalysts, it should be immediately noted that the most active MOF catalysts are united not by any fundamental property of the MOF but by the metal foam substrate that they are deposited on 182,[332][333][334][335][338][339][340][341][342]346. The use of metal foams and other highsurface-area supports is problematic for performance benchmarking because the current density is a descriptor that assumes a flat catalyst.…”
mentioning
confidence: 99%
“…Analysis results indicated that the Mn and Fe distribute uniformly within the structure (Figure S3) and the stoichiometry of Fe/Mn is approximately in 2 : 1 (Tables S3, S4, and S10), consistent with the previous reports. [ 39 ] The phase purity of bulk samples and the repeatability of the synthesis method were verified by PXRD patterns (Figure S2).…”
Section: Resultsmentioning
confidence: 95%
“…[ 33 ] Previous studies have shown that Fe 3 ( μ 3 ‐O)‐cluster, which is easy to prepare and convenient to completely or partly replace Fe by a specific metal atom (M), could be viewed as one of the most popular secondary building units (SBUs) to construct chemical stable MOFs with heterometallic synergy. [ 38‐43 ] To this regard, we attempt to introduce Mn into Fe 3 ( μ 3 ‐O) SBU and finally get Fe 3– x Mn x ( μ 3 ‐O)‐cluster based MOFs with high chemical stability and catalytic activity in oxidative coupling of amines.…”
Section: Background and Originality Contentmentioning
confidence: 99%